2019
DOI: 10.1021/acssuschemeng.8b05020
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-Assisted Fabrication of N-Doped Graphene-Supported Uniform Multipetal PtAg Nanoflowers for Enhanced Ethanol and Ethylene Glycol Oxidation

Abstract: The pursuit of efficient electrocatalysts with better activity, stability, and controllable morphology and size for alcohol oxidation is of decisive significance yet challenging for the application of direct alcohol fuel cells (DAFCs) in large scale. Herein, a series of glycine-assisted N-doped graphene (NG)-supported multipetal PtAg nanoflowers (NFs) has been successfully engineered to serve as high-performance electrocatalysts for ethanol electrooxidation and ethylene glycol electrooxidation catalysis. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 64 publications
(98 reference statements)
0
30
0
Order By: Relevance
“…In addition to Pt, the positive effect of nitrogen‐doped carbon materials has also been confirmed by the high performance of highly dispersed PtAg NG and PtSn NPs on NG for EOR and the ethylene glycol oxidation reaction (EGOR) . Compared with the PtAg, PtAg NPs deposited on the NG are more uniformly distributed with smaller size (Figure ) . In addition, the peak current density of G‐A PtAg/NG (3598.4 mA mg −1 ) is 1.33 and 3.61 times higher than those of G‐A PtAg and commercial Pt/C, respectively.…”
Section: Heteroatom‐doped Carbon Supportsmentioning
confidence: 97%
“…In addition to Pt, the positive effect of nitrogen‐doped carbon materials has also been confirmed by the high performance of highly dispersed PtAg NG and PtSn NPs on NG for EOR and the ethylene glycol oxidation reaction (EGOR) . Compared with the PtAg, PtAg NPs deposited on the NG are more uniformly distributed with smaller size (Figure ) . In addition, the peak current density of G‐A PtAg/NG (3598.4 mA mg −1 ) is 1.33 and 3.61 times higher than those of G‐A PtAg and commercial Pt/C, respectively.…”
Section: Heteroatom‐doped Carbon Supportsmentioning
confidence: 97%
“…Furthermore, recent observations demonstrated that the activity and stability are significantly enhanced through doping nonmetal elements such as boron, nitrogen, sulfur, into graphene due to the strong chemical binding between catalyst and support and the electronic structure modification of the catalysts [136–142] . Nitrogen doped graphene (NG) as a support for PtAg nanostructures have been engineered to act as high‐performance electrocatalysts to EOR and EGOR (Figure 7b) [143] . The MA toward EOR and EGOR reaches up to 3598.4 and 4587.2 mA mg −1 , respectively.…”
Section: Advanced Strategies For High‐performance Aor Electrocatalystsmentioning
confidence: 99%
“…The surface effect and ultrathin structure endow 2 D nanostructures with fascinating physicochemical properties that are inaccessible to their 0 D, 1 D, and 3 D counterparts . Therefore, the fabrication of nanomaterials with unique 2 D morphology has attracted intense research interest in recent years.…”
Section: Two‐dimensional Nanostructuresmentioning
confidence: 99%